A study on determinants of bond yield in Malaysia / Nurul Jannah Arifin and Nurul Atikah Yaacob - Arifin, Nurul Jannah; Yaacob, Nurul Atikah (Faculty of Business and Management, 2018)
Since gaining independence in 1957, Malaysia has successfully diversified its economy from one that was initially agriculture and commodity-based, to one that now plays host to robust manufacturing and services sectors that have propelled it to become a leading exporter of electrical appliances, electronic parts and components. Malaysia is one of the most open economies in the world, with a trade to GDP ratio averaging over 140 percent since 2010. Openness to trade and investment have been instrumental in employment creation and income growth, with about 40 percent of jobs in Malaysia linked to export activities. Malaysia’s near-term economic outlook remains favorable, reflecting a well-diversified and open economy that has successfully weathered the impact of external shocks. This is bolstered by strong macroeconomic management, with low and stable inflation and on-track fiscal consolidation. Domestic demand is expected to continue to anchor economic growth, supported by continued income growth and a stable labor market, while an improving external environment would contribute positively to demand for Malaysia’s tradable goods and services. Multiple linear regressions model is applied to study the relationship between explanatory variables (coupon rate, liquidity risk, inflation, exchange rate, and interest rate) and explained variable (bond yield in Malaysia). Empirical results show that as from the equation, it is found that independent variable for Coupon rate (CR) has significant relationship with bond yield in Malaysia (BM). Next is the independent variable of liquidity risk (LQ) where it shows an insignificant relationship with bond yield in Malaysia (BM) Apart from that, inflation (IF) also one of the independent variables which show’s an insignificant relationship with bond yield in Malaysia (BM). Other independent variable is exchange rate (EX) and interest rate (R) shows the result of insignificant